Westonci.ca offers fast, accurate answers to your questions. Join our community and get the insights you need now. Connect with professionals on our platform to receive accurate answers to your questions quickly and efficiently. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

IF Y = e ^ (- 3x) then prove that (d ^ 2 * y)/(d * x ^ 2) + (dy)/(dx) - 6y = 0​

IF Y E 3x Then Prove That D 2 Yd X 2 Dydx 6y 0 class=

Sagot :

Choncc

Step-by-step explanation:

dy/dx = -3e^(-3x) = -3y

d^2y/dx^2 = 9e^(-3x) = 9y

The equality becomes

-3y +9y -6y = 0

Which is true, 0=0